Continuous Flow Conversion of Glycerol into Chemicals: An Overview - Len, Christophe; Delbecq, Frederic; Cara Corpas, Cristobal; Ruiz Ramos, Encarnacion (Synthesis, 2018)
This report highlights the recent advances for glycerol valorization to valuable products in liquid phase continuous flow systems using different types of catalysts and processes. The main biobased chemicals obtained from glycerol, such as acrolein, lactic acid, dihydroxyacetone, propanediols, glycerol carbonate, solketal, acetin, alkyl ethers, and oligomers, will be presented.1 Introduction2 Continuous Dehydration2.1 Without Added Catalyst2.2 With Acid Catalyst3 Continuous Oxidation4 Continuous Hydrogenolysis5 Continuous Carbonatation6 Continuous Ketalization7 Continuous Esterification8 Continuous Etherification9 Continuous Oligomerization10 Outlook11 Conclusion
Keywords: glycerol; continuous flow; green chemistry; catalysis